2023
DOI: 10.1111/gcb.16628
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the drivers of continental mammalian endemism

Abstract: Endemic species and species with small ranges are ecologically and evolutionarily distinct and are vulnerable to extinction. Determining which abiotic and biotic factors structure patterns of endemism on continents can advance our understanding of global biogeographic processes, but spatial patterns of mammalian endemismhave not yet been effectively predicted and reconstructed. Using novel null model techniques, we reconstruct trends in mammalian endemism and describe the isolated and combined effects of physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 89 publications
1
11
0
Order By: Relevance
“…Our results are consistent with previous studies that have identified montane regions as areas of high vertebrate species richness and endemism (e.g. Kafash et al, 2020; Rahbek et al, 2019; Shipley & McGuire, 2023). The Nigeria‐Cameroon mountains consist of dense humid rain forests and deep gorges flanked by towering mountains (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with previous studies that have identified montane regions as areas of high vertebrate species richness and endemism (e.g. Kafash et al, 2020; Rahbek et al, 2019; Shipley & McGuire, 2023). The Nigeria‐Cameroon mountains consist of dense humid rain forests and deep gorges flanked by towering mountains (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…Using WWF ecoregions for this study allowed us to divide the global community of mammals into assemblages of species that are likely to interact with each other and be influenced by similar ecological and physiographic processes, in contrast to other, arbitrary study units [12,51,52]. Ecoregions vary widely in size, but ecoregion area has little effect on mammalian endemism patterns not already explained by species richness patterns [13].…”
Section: Methods (A) Study Extent and Spatial Unitsmentioning
confidence: 99%
“…The abiotic, environmental pattern of vertebrate endemism on continental scales is well studied [13][14][15][16][17]. However, the biological mechanisms underlying the global pattern of endemism is still unclear, and little consensus has been reached on how the biotic, functional traits of vertebrate species within endemism hotspots might covary with this pattern [15,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations